ByzRev 06.2024.074: Christos Malatras, Social Stratification in Late Byzantium: (Edinburgh Byzantine Studies). Edinburgh: Edinburgh University Press, 2023. - Estangüi Gómez, Raúl (The Byzantine Review, 2024)
Christos Malatras, Social Stratification in Late Byzantium (Edinburgh Byzantine Studies). Edinburgh: Edinburgh University Press, 2023. 608 pp., 12 b/w ill., 29 b/w tables. – ISBN 978-1-474-46088-0